2016
DOI: 10.1186/s12957-016-0998-y
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET in the evaluation of response to nivolumab in recurrent non-small-cell lung cancer

Abstract: BackgroundNivolumab, an immune checkpoint inhibitor, is recently clinically applied to non-small cell lung cancer (NSCLC) treatment, and this causes T cell activation and T cell infiltration to tumor tissue through the blockade of the interaction between programmed cell death 1 (PD-1) and programmed cell death ligand 1 (PD-L1). 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET) sometimes shows false positive because of the recruitment of neutrophils, lymphocytes, and macrophages. To date, there is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Therefore, it is necessary to determine the effect of anti-PD-1 treatment on the uptake of [ 18 F]FDG, a marker of glucose uptake in cells (e.g., effector immune cells and cancer cells). Clinical studies reported that immune checkpoint inhibitors increased [ 18 F]FDG uptake; however, other studies showed the opposite effect [22][23][24][25]. In this study, Fig.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Therefore, it is necessary to determine the effect of anti-PD-1 treatment on the uptake of [ 18 F]FDG, a marker of glucose uptake in cells (e.g., effector immune cells and cancer cells). Clinical studies reported that immune checkpoint inhibitors increased [ 18 F]FDG uptake; however, other studies showed the opposite effect [22][23][24][25]. In this study, Fig.…”
Section: Discussionmentioning
confidence: 43%
“…a Illustration of in vivo and ex vivo study timelines. b Tumor growth curves after anti-PD-1 or cGAMP treatment (n =[14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Data of the non-treatment group and anti-PD-1 treated group were quoted from[11].…”
mentioning
confidence: 99%
“…Although little is known about PERCIST criteria with respect to response to immunotherapy of NSCLC, there are a few studies or case reports describing its role in evaluating response to immune checkpoint inhibitors [15,25,[28][29][30]. In a recent study, 24 patients treated with PD-1 blockade (nivolumab) were investigated at baseline and 1 month after the start of treatment [15].…”
Section: Discussionmentioning
confidence: 99%
“…Because PD-1 inhibition increases glucose metabolism of immune cells and reduces cancer cell metabolism (23,29), 18 F-FDG uptake could be used for early treatment response evaluation. Recently, several studies showed the feasibility of applying 18 F-FDG PET in lung cancer patients as a tool for early response monitoring of immunotherapy (32,33). A recent finding of increased 18 F-FDG uptake in lymphoid tissue associated with immunotherapy response could also support the feasibility of 18 F-FDG PET as a valuable biomarker for response monitoring based on the mechanism of competitive 18 F-FDG uptake between immune cells and cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%